Screw Modification On Plastic Extruder Machine - Devi Andriani; Tri Pratomo; Muhammad Ariyanto; Diky Rahmat Suhendra; Nurhaidah Nurhaidah; Sukhma Kusuma Dewi (Universitas Muhammadiyah Metro, 2025)
Plastic extruder machine is a machine that processes material changes from the form of plastic making into extruded changes from solid to liquid form. In the plastic extruder machine there are many machine components used. The components found in the plastic extruder machine are the frame, reduction gear, puller roller, bearing, v-belt, electric motor, pulley, stepper, clutch, air chamber, nozzle, feeder, compression spring, panel box and screw. This study uses an experimental method by changing the screw diameter which was originally 37 mm to 41 mm in addition to changing the diameter size, changes were also made to the screw pitch size which was originally 12 mm to 14 mm. The modified screw that was tested using PLA material with a rotation of 38 rpm produced a flow rate of 0.00129 m ^ 3 / s with a maximum pressure of 10.2866 Mpa. While the screw before modification produced a flow rate of 0.000921 m^ 3 / s and a maximum pressure of 9.5151 Mpa. From the data obtained from the screw, the modification results obtained quite good results compared to the screw before modification.